Management modalities of isolated liver injury in blunt abdominal trauma - Mangukiya, Lalji; Astik, Hardik (International Surgery Journal, 2019)
Background: The liver is one of the most commonly injured organ in blunt abdominal trauma. Management of liver injury due to blunt abdominal trauma has been dramatically evolved in recent years. Dramatic change from operative management to non-operative management has improved survival in these patients, becoming the standard of care for most liver injuries. Methods: A retrospective study of the patients admitted with the diagnosis of isolated liver injury due to blunt abdominal trauma between 2013-2018. Data collected of 30 patients of isolated liver injury who either treated conservative management of operative management. Variable analyzed included demographic data, mechanism of injury, associated injury, conservative treatment, operative treatment, morbidity, mortality, and hospital stay. Results: A total of 30 patients were analyzed of isolated liver injury due to blunt abdominal trauma, 27 patient sustained minor liver injury (grade I, II and III), whereas 3 patients had major liver injury (grade IV, V and VI). 25 cases due to road traffic accident and 5 cases were due to falls from a height. 27 patients with American Association for the surgery of trauma grade I, II, III and 2 patients with grade IV, V managed conservatively, surgical intervention required in 1 patient with grade V, mortality occurred in 1 patient out of 29 who were treated conservatively. Conclusions: Isolated liver injury is common in the blunt abdominal trauma patient. Most of the patients with the liver injury with hemodynamically stable treated conservatively. Only a few of them require surgical management if they are hemodynamically unstable.